2013
DOI: 10.1007/s00436-013-3383-6
|View full text |Cite
|
Sign up to set email alerts
|

Current drug targets for helminthic diseases

Abstract: More than 2 billion people are infected with helminth parasites across the globe. The burgeoning drug resistance against current anthelmintics in parasitic worms of humans and livestock requires urgent attention to tackle these recalcitrant worms. This review focuses on the advancements made in the area of helminth drug target discovery especially from the last few couple of decades. It highlights various approaches made in this field and enlists the potential drug targets currently being pursued to target eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 114 publications
0
26
0
Order By: Relevance
“…On the other hand, some studies have suggested that treatment with nematicides as albendazole may constitute an effective therapy [10–13]. However, the worldwide development of resistance to chemical anthelmintic drugs [14] and a current social demand for natural therapeutic products has increased the search for new biocide molecules. Plant products are the basis of traditional medicine and the only health resource available in many communities from developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some studies have suggested that treatment with nematicides as albendazole may constitute an effective therapy [10–13]. However, the worldwide development of resistance to chemical anthelmintic drugs [14] and a current social demand for natural therapeutic products has increased the search for new biocide molecules. Plant products are the basis of traditional medicine and the only health resource available in many communities from developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Research study of the helminths is aiming to identify potential and drug gable targets through biochemical, biophysical, genomic, proteomic, in vivo and vitro experiments in animal models 13 . Therefore, in the last few years, they recommended to use of biological substance instead of chemicals in the dominate on parasites because of that these natural products have potency against different pathogens and mostly are safe to use 14,15 .…”
mentioning
confidence: 99%
“…Successful compounds would be inhibitors of an essential or unique bacterial enzyme which has no mammalian homologue. The number of drug targets for helminthic diseases so far identified is few (63), and the threats are compounding with burgeoning resistance against the existing drugs (64,65). The parasites and microorganisms are becoming increasingly resistant to the available antibiotics, which makes the search for novel antibiotic agents inevitable (66).…”
mentioning
confidence: 99%